Evaluating Chemical Mitigation of Porcine Epidemic Diarrhea Virus (PEDV) in Swine Feed and Ingredients - R. A. Cochrane; S. S. Dritz; J. C. Woodworth; A. R. Huss; C. R. Stark; R. A. Hesse; Jianqiang Zhang; M. D. Tokach; J. Bai; C. K. Jones (Kansas Agricultural Experiment Station Research Reports, 2015)
Porcine Epidemic Diarrhea Virus (PEDV) is primarily transmitted by fecal-oral contamination. Research has confirmed swine feed or ingredients as potential vectors of transmission, so strategies are needed to mitigate PEDV in feed. The objective of this experiment was to evaluate the effectiveness of various chemical additives to prevent or mitigate post-processing PEDV contamination in swine feed and ingredients. Treatments were arranged in a 7 × 4 factorial with seven chemical treatments and four feed matrices. The chemical treatments included: negative control with no chemical addition, 0.3% commercial formaldehyde product, 1% sodium bisulfate, 1% sodium chlorate, 3% custom organic acid blend (OA), 2% custom essential oil blend (EO), and 2% custom medium chain fatty acid blend (MCFA). The four matrices included a complete swine diet, blood meal, meat and bone meal, and spray-dried animal plasma. Matrices were first chemically treated, then inoculated with PEDV, stored at room temperature, and analyzed by RT-PCR on d 0, 1, 3, 7, 14, 21, and 42 post inoculation. Formaldehyde, MCFA, EO, and OA addition each decreased RNA concentration of PEDV compared to the control (P<0.05), with formaldehyde being the most effective on d 0. Feed matrix appears important in PEDV retention, as RNA concentrations were lower in the swine diet and blood meal than meat and bone meal or spray-dried animal plasma on d 0 (P<0.05). Additionally, PEDV stability over time was influenced by matrix as RNA concentrations were greater by d 42 for spray-dried animal plasma and meat and bone meal than the complete swine diet and blood meal. In summary, time, formaldehyde, MCFA, EO, and OA all enhance the RNA degradation of PEDV in swine feed and ingredients as measured by RT-PCR, but their effectiveness varies within matrix. Notably, the MCFA was equally as successful at mitigating PEDV as a commercially-available formaldehyde product.
Keywords: PEDV; chemical treatment; feed matrix; swine